Role of Intermittent Fasting in the Management of the Diabetes Mellitus Type 2 Patients in Karachi - Fareeha Shahid, Umer Shabbir, Muhammad Ahmed Sajid Tarrar, Eman Zahra, Ahmad Zohad, Sangeen Naseer (Pakistan Journal of Medical & Health Sciences, 2023)
To determine the role of intermittent fasting in managing Diabetes Mellitus Type 2 patients in Karachi. Methodology: It was a cross-sectional study conducted at Bahria University Health Sciences Campus, Karachi with total duration of three months from February 2022 to May-2022. After IRB approval random sampling technique was used to recruit subjects. 156 patients with DM type II were part of the study out of which 102 were in fasting among them 75 patients found intermittent fasting beneficial in managing blood glucose and symptoms, remaining 27 did not find it beneficial. Data Analysis was conducted by using SPSS version 25. Results: A total of 156 patients with DM type II were part of the study out of which 102 were fasting among them 75 patients found intermittent fasting beneficial in managing blood glucose and symptoms, remaining 27 did not find it beneficial thus 73.5 % patients were better able to manage DM II with intermittent fasting. There was no association between the beneficial effects of intermittent fasting with a specific type. Conclusion: Intermittent Fasting is beneficial for diabetes mellitus type II patients which proves our alternate hypothesis, but there is no specific type of intermittent fasting associated with it being beneficial. As long as a patient of DM II was observing periods of intermittent fasting, it has been show a clear evident that intermittent fasting plays a key role in the management of diabetes mellitus type II patients. Keywords: Diabetes Mellitus, DM, Intermittent Fasting, Control of DM, Fasting